An assessment of website quality at Nigerian polytechnics and colleges of education - Ibhadode, Oseikhuemen; Opesade, Adeola (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2022)
This study assessed the quality of the websites of Nigerian polytechnics and colleges of education. Using two web diagnostic tools, SEOptimer and W3C Markup Validation Service, a total of 213 sites were evaluated in terms of six performance indicators: search engine optimisation (SEO), usability, operational performance, social media integration, security, and HTML validation. The weakest performance across the sites of both polytechnics and colleges of education was found to be with respect to social media integration, with the vast majority of sites in both categories making no use of social media. The other two indicators against which sites in both categories of institutions tended to perform poorly were SEO and operational performance. The two areas where the sites in both institutional categories generally scored well were usability and HTML validation. Meanwhile, for the security indicator, the performance was highly variable among both polytechnic and college of education sites, with significant numbers of both strong and weak scores for sites. It was also found that polytechnic sites outperformed college of education sites on SEO to a statistically significant degree (bearing in mind that both categories of sites were weak in this area). It was also found that, among the polytechnic sites, the sites of the state government-owned institutions outperformed, to a statistically significant degree, the sites of the privately owned institutions in their operational performance measure.